The status of training: training agency service patterns compared to those of managed behavioral health care organizations - Horton, Jamie Ronnée, author; Rosén, Lee, advisor; Boyer, William N., committee member; Gilliland, David I., committee member; Vacha-Haase, Tammi, committee member (Colorado State University. Libraries, 2002)
The dominance of managed behavioral health care in the mental health industry has led to concerns about the status of training for psychologists. The concern suggests that there are discrepancies between experiences in managed behavioral health care organizations (MBHOs) and pre-doctoral training agencies. This study examines discrepancies by comparing training agency service patterns to those of MBHOs. Service patterns included in the study are client demographic information, treatment length, diagnoses, and treatment events for years 1997-1999. The results are consistent with earlier findings and indicate that there are significant differences between training agencies and MBHOs for all variables. The findings have important implications for the training of psychologists, and recommendations for training and future research are provided.
Keywords: psychotherapy; adult education; continuing education; health care; behavioral sciences; organizations; studies; research; internships; group therapy; psychology; students; task forces; therapists; trends; health care policy; health care delivery; mental disorders; statistics; age; cooperation; clinics; counseling psychology; clinical psychology; copyright; databases; data collection; mental health; health care management; health services; education; fees and charges; variance analysis; mental health care; ethnicity